Sex Differences in NeuN- and Androgen Receptor-Positive Cells in the Bed Nucleus of the Stria Terminalis are due to Bax-Dependent Cell Death - Holmes, Melissa M. (2008)
The principal nucleus of the bed nucleus of the stria terminalis (BNSTp) is larger in males than in females of several species. We previously demonstrated that in mice lacking the pro-death gene, bax, total BNSTp cell number is increased and sex differences in cell number are eliminated. This suggests that Bax-dependent cell death underlies sexual differentiation of the BNSTp. However, it is not known what cells in the BNSTp are affected by bax deletion. Here we used immunohistochemistry and stereological techniques to quantify phenotypically-identified cells in the BNSTp of adult male and female bax -/- and bax +/+ mice. Sections were thionin-stained, or double-labeled for NeuN and GFAP to identify mature neurons and astrocytes, respectively; an additional series was labeled for androgen receptor (AR). As previously demonstrated, sex differences in BNSTp area and overall cell number were seen in wildtype mice, but absent in bax -/- animals. In addition, sex differences (favoring males) were present in the number of NeuN+ and AR+ cells in wildtype mice. Bax gene deletion significantly increased the number of NeuN+ and AR+ cells and reduced or eliminated the sex differences in these cell types. The number of astrocytes in the BNSTp was not sexually dimorphic, nor significantly affected by bax gene status, although there was a trend for more GFAP+ cells in bax -/- mice. Overall brain weight was also greater in bax -/- animals compared to controls. We conclude that the sex differences in neuron and AR+ cell number are due at least in part to Bax-mediated cell death. Increased NeuN+ and AR+ cell number in bax -/- mice suggests that supernumerary cells in bax knockouts differentiate similarly to those in wildtype mice, and retain the capacity to respond to androgens.